“Doing well” by “doing good”? Evidence from tourism-related firms in four South Asia countries - Tan, Siow-Hooi; Muzafar Shah Habibullah,; Choon, Shay-Wei; Azali Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study explores the corporate giving and financial performance nexus in tourism-related firms from four South Asia countries. Specifically, this study investigates if there exists an inverse U-shaped link between corporate giving and financial performance and assesses the potential bi-directional relationship between these two variables. Results generated from system-GMM estimator reveal that the effects of corporate giving on both ROA and Tobin’s Q are curvilinear. In particular, an inverse U-shaped relationship is observed, implying that firms are rewarded for their corporate giving engagement, which denotes “doing-good” leads to “doing well,” within a certain limit. Interestingly, this study also finds evidence that the firms which perform well financially are shown to engage less in corporate giving. Specifically, “doing-well” firms are shown to lead to lower level of “doing good,” supporting the management opportunity hypothesis. This study has policy implications in pushing for further CSR initiatives in other industries and emerging markets.